Creative Entanglements: Riffing With Posthuman Arts-Based Inquiry - Wainwright, Richard; Stevens, Shannon (Art/Research International, 2026)
This paper looks into evolving practices in arts-based research (ABR) through the lens of Posthuman Arts-Based Inquiry (PABI) and its principle of experimental recombinatoriality, referred to here as “riffology”. By pushing back on anthropocentric assumptions, PABI brings in human and nonhuman forces alike, generating a more expansive approach to creativity and knowledge production. Drawing on DeleuzoGuattarian philosophy, new materialist perspectives, and post-qualitative research, we treat artmaking as an ontological event rather than mere representation. In doing so, PABI challenges established boundaries within ABR, foregrounding shared agency and ethical obligations that extend across human, technological, and ecological domains. Through practical examples and theoretical grounding, this paper demonstrates how PABI reimagines creative inquiry amid planetary crises, ultimately offering a posthuman critical pedagogy with the potential to transform both educational and societal landscapes.